Intelligence science and big data engineering. 5th International Conference, IScIDE 2015 Suzhou, China, June 14-16, 2015 ; revised selected papers /: 5th International Conference, IScIDE 2015 Suzhou, China, June 14-16, 2015 ; revised selected papers. Big data and machine learning techniques : Part II, ([2015]) - Unknown
No abstract available